IDENTIFICATION OF FLEXIBLE PAVEMENT DAMAGE LEVEL IN ROUTINE MAINTENANCE OF ROADS BANTAENG DISTRICT - Maryam H; Minarni (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2018)
Road maintenance is carried out continuously throughout the year and carried out as soon as possible when the damage is not widespread. Road maintenance is managed directly by the PUPR Service for Roads and Bridges in Bantaeng Regency through routine maintenance based on self-management funds. The pavement identification benchmarks used include the condition of flexible pavement damage and district road pavement damage which are included in the low traffic category. This study aims to: (1). Identify the condition of road pavement damage in routine road maintenance activities in Bantaeng Regency. (2). Analyzing alternatives for routine maintenance of district roads with a self-managed system. Using the Bina Marga method and the Pavement Condition Index (PCI) method to identify the level of damage and handling in routine maintenance with a self-managed system. The result of the damage number of the Bina Marga method is 17 so that the value of the road condition is 6 with the type of damage to crocodile skin cracks. While the results of the priority value of 5 < 7 which states the condition of pavement damage are grouped in a routine maintenance program with a self-managed system. The results of the survey of the SDI value of 100 are grouped in a lightly damaged condition in the category of routine maintenance. The results of the identification of damage conditions using the PCI method obtained crocodile skin cracks, obesity, box cracks, hollows, subsidence, edge cracks, fillings, aggregate wear and holes. Alternative treatment requires a routine maintenance program that is carried out on a self-managed basis.